Nitrogen Supply Alters Rice Defense Against the Striped Stem Borer Chilo suppressalis - Zheng, Yueqin; Zhang, Xiyong; Liu, Xin; Qin, Ningning; Xu, Kaifang; Zeng, Rensen; Liu, Jian; Song, Yuanyuan (Frontiers in Plant Science, 2021)
Plant nutrition status is closely associated with plant defense against insect herbivores. However, the way nitrogen supply regulates rice anti-herbivore is not clear. This study investigated the effects of low (LN, 0.3 mM) and high (HN, 3 mM) nitrate levels on rice resistance against the striped stem borer Chilo suppressalis (SSB), one of the major destructive rice pests. Seven-day-old rice seedlings were cultured with different nitrate levels for 30 days and then inoculated with third instars of SSB. LN significantly enhanced rice anti-herbivore defense and lowered the total nitrogen content in the plants, but increased the content of free amino acids after SSB infestation. Additionally, LN significantly increased the accumulation of phenolic acids and flavonoids, especially lignin, resulting in enhanced constitutive defense in SSB-infested plants. SSB feeding led to rapid accumulation of secondary metabolites. HN application led to accumulation of metabolites derived from cinnamic acid, ρ-coumaric acid, ρ-coumaric CoA, feruloyl CoA and apigenin, while LN led to accumulation of metabolites derived from 3-dehydroquinic acid, phenylalanine, acetyl CoA and aspartic acid. Collectively, our finding suggests nitrogen deficiency enhances rice anti-herbivore defense via constitutive defense by accumulation of phenolic acids and flavonoids.